Overcoming Overthinking: Psychological Strategies for a Calmer Mind - Setiawati, Noor Lusty Putri; Mulyana, Mulyana (Psikologiya Journal, 2025)
Overthinking or the tendency to overthink is a psychological phenomenon that is increasingly common in modern society. This study aims to deeply understand the individual experience in dealing with overthinking and the psychological strategies used to overcome it. Using a descriptive qualitative approach, data were collected through in-depth interviews with 8 informants aged 20–35 years who had participated in interventions such as Cognitive Behavioral Therapy (CBT), mindfulness, or other relaxation techniques. The results of thematic analysis showed that overthinking was triggered by uncertainty about the future, social pressure, and fear of failure, and had an impact on mental and physical health. The strategies used included cognitive (cognitive restructuring, journaling), emotional (mindfulness, meditation), and behavioral (diversionary activities, healthy routines) approaches. Although effective, these strategies have limitations in terms of consistency and social support. This study emphasizes the importance of an integrative approach based on CBT and mindfulness in overcoming overthinking and encouraging mental health policies that are more responsive to the psychosocial dynamics of modern society